2020
DOI: 10.3390/agriculture10080328
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Physiological and Biochemical Responses to Salt Stress of Eggplant (Solanum melongena) and Its Rootstock S. torvum

Abstract: This study investigated the physiological and biochemical responses to salinity stress of Solanum melongena and its wild relative, Solanum torvum, commonly used as eggplant rootstock. Young plants of both species were watered during 25 days with NaCl aqueous solutions at the following four final concentrations: 0 (for the controls), 100, 200, and 300 mM. Plant growth parameters, photosynthetic pigments content, monovalent ion concentrations in roots and leaves, leaf levels of osmolytes (proline and total solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 61 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Apart from the evaluation of growth and development traits, several antioxidant enzymes, such as catalase and peroxidase, play a main role in reducing oxidative damage caused by stress [31]. In addition, osmolytes such as proline are known to be involved in maintaining the osmotic balance under salinity stress [32].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the evaluation of growth and development traits, several antioxidant enzymes, such as catalase and peroxidase, play a main role in reducing oxidative damage caused by stress [31]. In addition, osmolytes such as proline are known to be involved in maintaining the osmotic balance under salinity stress [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, plant tolerances to saline vary widely from soil to soil and from salt type to salt type [5] as well as differences among crop species and growth stages. Crop species show the big differences in tolerance to salinity [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, under salinity stress Na + ions were largely translocated to the shoot; this was revealed from the relatively higher TF compared to that of untreated plants, while application of selected bioinoculum to salt-stressed eggplants relatively decreased the TF of Na + ions with respect to saline pots. The Solanum trovum resistance mechanism to salinity was moderately based on the active transport of toxic ions to the leaves and, probably, a better capacity to store them in the vacuoles [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proline content was increased in two genotypes (Barcelone and Threa) of S. melongena L. under salinity stress [ 53 ]. Similarly, leaf proline levels increased significantly in S. melongena and S. insanum in response to different salt stress treatments, moreover it is suggested that S. insanum is more tolerant to salinity stress due to its capacity to accumulate proline and to a lesser extent Na + and Cl − [ 44 ].…”
Section: Discussionmentioning
confidence: 99%